Gestión administrativa y su relación con la niñez y adolescencia en el departamento de cultura y deporte en la ciudad de Quevedo, año 2013 - Pluas Bahamonde, Mónica Marilú (2013)
Today the good management of administrative processes is vital in the progress of every business, and in every organization. The State, as an organization, is no exception, given its complexity, should be the first to have a good system of information management, so unfortunately there is found primarily in large parts of the developing nations of the world. This is largely due to the administration that usually governments, this detached to the principles governing the administration of a company, when the opposite should apply the guidelines and administrative principles of the companies that have reached an important and stable position in a world of constant change. Therefore, this work fulfills the purpose of conducting the evaluation and analysis of the administration of the Department of Culture and Sports of GAD Quevedo and Its Impact on Children and Adolescents with Canton. Which contains the following main topics: CHAPTER I PROBLEM DEFINING, a brief analysis in this detailed and problems encountered in the Department, its causes and effects are described. CHAPTER II THEORETICAL FRAMEWORK: It is based on theoretical concepts, which helped to identify the functions and administrative processes, which served as a guide in the evaluation of the Administrative Management Department of Culture and Sports, SWOT Analysis. CHAPTER III RESEARCH METHODOLOGY This details the methods, types and design research, and shows that population determines how to reach results. CHAPTER IV. Results and Discussions Comprising the bulk of the research, which is the development of objectives in order to obtain deductions of the Administrative Management Department of Culture Gad of Quevedo.